Lola Levine, drama queen - Brown, Monica, 1969-; Dominguez, Angela N. (New York : Little, Brown and Co., 2016)
"Lola Levine is given a non-speaking part after getting stage fright during her class play audition. She saves the play after a couple of obstacles with the help of her grandmother"--Provided by the publisher.
K-3
660
Accelerated Reader AR
Reading Counts RC
Keywords: Stage fright -- Fiction; Theater -- Fiction; School stories; Family life -- Fiction